Legitimating practices: revisiting the predicates of police legitimacy - Huq, Aziz Z. (The British journal of criminology, 2017)
Procedural justice theory predicts a relationship between police behaviour, individuals’ normative evaluation of police and decisions to comply with laws. Yet, prior studies of procedural justice have rather narrowly defined the potentially relevant predicates of police behaviour. This study expands the scope of procedural justice theory by considering a broad array of policing components, including unobserved actions such as electronic surveillance, respecting the limits of one’s legal authority, and the unequal or equal distribution of policing resources between different groups. Analysing data from a national probability sample of adults in England and Wales, we (1) present a comprehensive investigation of the heterogeneous elements of policing related to legitimacy judgments and (2) contribute to debate about the nature of legitimacy.